Bioaugmentation removal and microbiome analysis of the synthetic estrogen 17α-ethynylestradiol from hostile conditions and environmental samples by Pseudomonas citronellolis SJTE-3. (March 2023) - Peng, Wanli; Lin, Shuangjun; Deng, Zixin; Liang, Rubing
Abstract: Synthetic estrogens are emerging environmental contaminants with great estrogenic activities and stable structures that are widespread in various ecological systems and significantly threaten the health of organisms. Pseudomonas citronellolis SJTE-3 is reported to degrade the synthetic estrogen 17α-ethynylestradiol (EE2) efficiently in laboratory conditions. In this work, the environmental adaptability, the EE2-degrading properties, and the ecological effects of P. citronellolis SJTE-3 under different hostile conditions (heavy metals and surfactants) and various natural environment samples (solid soil, lake water, and pig manure) were studied. Strain SJTE-3 can tolerate high concentrations of Zn 2+ and Cr 3+, but is relatively sensitive to Cu 2+ . Tween 80 of low concentration can significantly promote EE2 degradation by strain SJTE-3, different from the repressing effect of Triton X-100. High concentration of Tween 80 prolonged the lagging phase of EE2-degrading process, while the final EE2 removal efficiency was improved. More importantly, strain SJTE-3 can grow normally and degrade estrogen stably in various environmental samples. Inoculation of strain SJTE-3 removed the intrinsic synthetic and natural estrogens (EE2 and estrone) in lake water samples in 4 days, and eliminated over 90% of the amended 1 mg/L EE2 in 2 days. Bioaugmentation of strain SJTE-3 in EE2-supplied solid soil and pig manure samples achieved a removal rate of over 55% and 70% of 1 mg/kg EE2 within 2 weeks. Notably, the bioaugmentation of extrinsic strain SJTE-3 had a slight influence on indigenous bacterial community in pig manure samples, and its relative abundance decreased significantly after EE2 removal. Amendment of EE2 or strain SJTE-3 in manure samples enhanced the abundance of Proteobacteria and Actinobacteria, implying their potential in utilizing EE2 or its metabolites. These findings not only shed a light on the environment adaptability and degradation efficiency of strain SJTE-3, but also provide insights for bioremediation application in complex and synthetic estrogen polluted environments. Graphical abstract: Image 1 Highlights: Pseudomonas citronellolis SJTE-3 can tolerate high concentration of Zn 2+ and Cr 3+ . Tween 80 promoted EE2 removal by strain SJTE-3 as surfactant or co-utilized energy. Strain SJTE-3 removed EE2 effectively from solid soil, lake water and manure samples. Strain SJTE-3 is ecologically safe to the indigenous bacteria community in manure. Abundance of Proteobacteria and Actinobacteria enhance for EE2-utilizing potential.